Preauricular pilomatrixoma in a 3 year-old girl: A case study - Hirbod, H; Ameli, F; Swamintanhan, M; Goh, BS (Bangladesh Journal of Otorhinolaryngology, 2012)
Objectives: To report a case of preauricular pilomatrixoma in a 3-year-old girl. Methods: Retrospective review on a case report Results: A three-year-old girl presented with six month history of painless right pre-auricular swelling that was gradually increasing in size. The mass was small, soft, non tender with normal overlying skin. She underwent excisional biopsy of lesion and histopathological examination showed pilomatrixoma. She was well post operatively and no recurrence after 2 years of follow up. Conclusion: Pilomatrixoma is often misdiagnosed clinically as epidermoid cyst, sebaceous cyst, dermoid cyst, foreign body reaction, calcification in lymph node, fat necrosis, pyogenic granuloma, chalazion and keratoacanthoma, but a high index of suspicion and careful histological examination of its characteristic clinical feature can help clinicians to differentiate it from other tumors. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10426 Bangladesh J Otorhinolaryngol 2012; 18(1): 84-86